Resection of the tumor in the trigone of the lateral ventricle via the contralateral posterior interhemispheric transfalcine transprecuneus approach with multi-modern neurosurgery technology: a case report - Song, Yunfei; Wang, Zhen; Zhang, Jun; Cui, Xiaopeng; Wu, Zhuolin; Zhao, Zilin; Chen, Yan; Zhang, Suqin; Zhu, Xiaowei; Wang, Zhitao; Zhang, Huijie; Gao, Chao; et al. (Frontiers in Surgery, 2024)
Choroid plexus papilloma (CPP) is a rare benign intracranial tumor origin that predominantly manifests in the lateral ventricle in children, accounting for 0.3-0.6% of all primary intracranial tumors. It is extremely rare to have the CPP in the trigone of the lateral ventricle through the contralateral posterior interhemispheric transfalcine transprecuneus approach (PITTA). Herein, we report this rare case. A 7-year-old girl presented with headache. Magnetic resonance imaging of the brain showed periatrial lesions, and histopathological examination confirmed CPP (WHO grade I). The contralateral PITTA is a safe, effective, reasonable, and appropriate for some lesions in the trigone of the lateral ventricle. It provides a wider surgical angle (especially for the lateral extension) and reduces the risk of disturbance of the optic radiation compared with the conventional approaches. The use of multiple modern neurosurgical techniques, including interventional embolization, intraoperative navigation, microscope, and electrophysiological monitoring, make the procedure much easier and more accurate, and the neuroendoscope adds to the visualization of the microscope and can reduce surgical complications.